Constitutional Deliberative Democracy in Europe - Reuchamps, Min; Suiter, Jane (ECPR Press, 2016)
From small-scale experiments, deliberative mini-publics have recently taken a constitutional turn in Europe. Iceland and Ireland have turned to deliberative democracy to reform their constitutions. Estonia, Luxembourg and Romania have also experienced constitutional process in a deliberative mode. In Belgium the G1000, a citizen-led initiative of deliberative democracy, has fostered a wider societal debate about the role and place of citizens in the country’s democracy. At the same time, European institutions have introduced different forms of deliberative democracy as a way to connect citizens back in. These empirical cases are emblematic of a possibly constitutional turn in deliberative democracy in Europe. The purpose of this book is to critically assess these developments, bringing together academics involved in the designing of these new forms of constitutional deliberative democracy with the theorists who propagated the ideas and evaluated democratic standards.